Spectroscopic properties of inorganic and organometallic compounds : techniques, materials and applications. - Yarwood, J., 1939-, editor; Douthwaite, Richard, editor; Duckett, Simon B., editor (Cambridge : Royal Society of Chemistry, 2014)
Includes bibliographical references